2001
DOI: 10.2105/ajph.91.9.1482
|View full text |Cite
|
Sign up to set email alerts
|

Differential HIV Risk in Bathhouses and Public Cruising Areas

Abstract: Distinguishing between sex venues previously treated as a single construct revealed a significant association between pattern of venue use and sexual risk. Targeting HIV prevention in the bathhouses would reach the segment of men at greatest risk for HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(160 citation statements)
references
References 13 publications
6
154
0
Order By: Relevance
“…27 With respect to contextual variables, risk reducers were less likely to have met sex partners in the prior 12 months at public cruising areas and via the Internet. This finding is consistent with prior research showing that MSM frequenting specific gay venues are more likely to engage in high risk sexual behaviors 28,29 and more often use substances during sex 30,31 compared to those who do not. Findings from the current study suggest that in addition to addressing psychosocial issues, effective HIV prevention interventions should consider ways to engage the MSM at greatest risk for HIV acquisition and transmission in their risky environments.…”
Section: Discussionsupporting
confidence: 91%
“…27 With respect to contextual variables, risk reducers were less likely to have met sex partners in the prior 12 months at public cruising areas and via the Internet. This finding is consistent with prior research showing that MSM frequenting specific gay venues are more likely to engage in high risk sexual behaviors 28,29 and more often use substances during sex 30,31 compared to those who do not. Findings from the current study suggest that in addition to addressing psychosocial issues, effective HIV prevention interventions should consider ways to engage the MSM at greatest risk for HIV acquisition and transmission in their risky environments.…”
Section: Discussionsupporting
confidence: 91%
“…Other investigators have found that MSM who seek sex in multiple venues (e.g., bathhouses and public cruising areas) are at greater risk for engaging in unprotected anal intercourse with nonprimary partners than are men seeking sex in only 1 venue. 40 Use of alcohol and other substances in offline settings such as bars can impair one's judgment regarding risk reduction. Perhaps "sensation seeking" 41,42 (i.e., the willingness to take risks to experience novel and intense sensations) or other personality characteristics [43][44][45] not measured in our study can explain the high levels of unprotected anal intercourse and substance abuse in this group.…”
Section: Discussionmentioning
confidence: 99%
“…They may be buffered, for example, both by individual-level material resources associated with their social class as well as by the protection conferred by their identity as upper class men, a mechanism we will describe in greater detail later. Other features of the physical environment that might uniquely influence the sexual behavior of MSM include public park spaces, which have been historically Bsafe^spaces for meeting sexual partners and having sex, 168 and alcohol outlet availability, as a strong association between drug and alcohol use and risky sexual behaviors among MSM exists.…”
Section: The Urban Environment and Sexual Behavior Of Msm: Applying Ementioning
confidence: 99%